EVALUASI DAN PERENCANAAN KEMBALI BENDUNG SAPON - Dyah Wahyu Apriani; Fajar Nugroho Utomo; Sri Eko Wahyuni; Siti Hardiyati (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Sapon weir, which located at Kulon Progo, Yogyakarta, is a hydraulic structure that its water supply is from Progo river. Sapon weir are used to flow through ± 1850 ha rice field area, from ± 2250 ha before at 2,3 m3/sec, and to fulfill the water needs in 4 sub districts at 0,2 m3/sec. The increasing function of Sapon weir from only covering the irrigation needs, to fulfilling the water needs it is the implementation of the regulation no 8 year 2005 about water resources. The analysis of flood design using Haspers Metod, FSR Jawa-Sumatera, HSS Nakayasu, HSS Gama 1 with flood design comparation from Pasing Capacity Metod that has 1123,96 m3/sec of flood discharge in hundred year periode (Q100). The design of Sapon weir consists of main dam, complement buildings and requirement water supply pump for 1383,97 m3/sec of flood discharge hundred years period. The differences of weir design change the weir dimensions and the complement buildings.